Unlocking iPhone Brand Loyalty and Extension Insights: Membuka Wawasan Loyalitas dan Perluasan Merek iPhone - Hasbullah, Hasbullah; Sriyono, Sriyono (Indonesian Journal of Innovation Studies, 2024)
This quantitative research investigates the influence of brand attitude, brand affect, and brand characteristic on consumer brand extension attitude, with brand loyalty as an intervening variable, specifically focusing on iPhone smartphones in Indonesia. Using Structural Equation Modeling-Partial Least Square (SEM-PLS), data from 400 iPhone users were analyzed. The study aims to bridge the gap in understanding consumer behavior towards smartphone products, particularly iPhones, in the Indonesian market. Findings indicate significant effects of brand attitude, brand affect, and brand characteristic on both consumer brand extension and brand loyalty. Furthermore, brand loyalty was found to mediate the relationship between these factors and consumer brand extension attitude. The study suggests that companies should innovate and maintain product characteristics to stay relevant in consumers’ minds, enhancing brand loyalty and consumer brand extension attitude, thus impacting marketing strategies and product development. Hightligh: iPhone Brand Perception Study: Analyzed factors affecting loyalty and brand extension attitude, Used SEM-PLS for data analysis. Consumer Behavior Insights: Explored iPhone brand perception in Indonesian market, Identified significant impacts on loyalty and extension attitude. Brand Management Implications: Emphasized innovation and differentiation, Insights for marketing strategies and product development. Keywords: Brand Attitude, Brand Affect, Brand Characteristic, Consumer Brand Extension, Brand Loyalty